Nitric Oxide Regulates Estrus Cycle Dependent Colonic Motility in Mice - Balasuriya, Gayathri K.; Nugapitiya, Saseema S.; Hill-Yardin, Elisa L.; Bornstein, Joel C. (Frontiers in Neuroscience, 2021)
Women are more susceptible to functional bowel disorders than men and the severity of their symptoms such as diarrhea, constipation, abdominal pain and bloating changes over the menstrual cycle, suggesting a role for sex hormones in gastrointestinal function. Nitric oxide (NO) is a major inhibitory neurotransmitter in the gut and blockade of nitric oxide synthase (NOS; responsible for NO synthesis) increases colonic motility in male mice ex vivo. We assessed the effects of NOS inhibition on colonic motility in female mice using video imaging analysis of colonic motor complexes (CMCs). To understand interactions between NO and estrogen in the gut, we also quantified neuronal NOS and estrogen receptor alpha (ERα)-expressing myenteric neurons in estrus and proestrus female mice using immunofluorescence. Mice in estrus had fewer CMCs under control conditions (6±1 per 15 min, n=22) compared to proestrus (8±1 per 15 min, n=22, One-way ANOVA, p=0.041). During proestrus, the NOS antagonist N-nitro-L-arginine (NOLA) increased CMC numbers compared to controls (189±46%). In contrast, NOLA had no significant effect on CMC numbers during estrus. During estrus, we observed more NOS-expressing myenteric neurons (48±2%) than during proestrus (39±1%, n=3, p=0.035). Increased nuclear expression of ERα was observed in estrus which coincided with an altered motility response to NOLA in contrast with proestrus when ERα was largely cytoplasmic. In conclusion, we confirm a cyclic and sexually dimorphic effect of NOS activity in female mouse colon, which could be due to genomic effects of estrogens via ERα.